(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Cost–benefit analysis (CBA) is a fundamental decision-making tool used to evaluate the financial and strategic viability of projects by comparing expected costs with anticipated benefits. Originating from the work of Jules Dupuit and later refined by scholars such as Alfred Marshall and the U.S. Corps of Engineers, CBA incorporates both tangible and intangible factors to determine whether a project is worthwhile. In today’s dynamic and competitive business environment, firms increasingly rely on CBA to guide strategic choices, enhance performance, and allocate resources effectively. This conceptual paper reviews key scholarly literature to explore how the principles of CBA can contribute to improved firm performance, particularly within the context of twenty-first-century organizational challenges. The study also highlights the relevance of applying strategic management accounting perspectives to CBA and proposes hypotheses for future research. The paper is especially significant for Iraq and other socioculturally connected Middle Eastern economies, offering theoretical and methodological insights into the relationship between strategic CBA applications and firm performance.